1992
DOI: 10.1093/ajcn/55.3.670
|View full text |Cite
|
Sign up to set email alerts
|

Role of fat oxidation in the long-term stabilization of body weight in obese women

Abstract: Two studies were performed to investigate the association between body fat mass and fat oxidation. The first, a cross-sectional study of 106 obese women maintaining stable body weight, showed that these two variables were significantly correlated (r = 0.56, P less than 0.001) and the regression coefficient indicated that a 10-kg change in fat mass corresponded to a change in fat oxidation of approximately 20 g/d. The second, a prospective study, validated this estimate and quantifies the long-term adaptations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
87
3
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 183 publications
(109 citation statements)
references
References 19 publications
14
87
3
5
Order By: Relevance
“…13 Baseline RQ (0.846 AE 0.048, min 0.743, max 0.960) was not related to age, weight BMI or BMR. Taking into account that fatness is usually considered as a determinant of macronutrient oxidation causing a RQ increase, 14 the lack of a relationship between RQ and BMI in this study might be due to the exclusion of obese women.…”
Section: Resultsmentioning
confidence: 93%
“…13 Baseline RQ (0.846 AE 0.048, min 0.743, max 0.960) was not related to age, weight BMI or BMR. Taking into account that fatness is usually considered as a determinant of macronutrient oxidation causing a RQ increase, 14 the lack of a relationship between RQ and BMI in this study might be due to the exclusion of obese women.…”
Section: Resultsmentioning
confidence: 93%
“…Indeed, it has been reported on numerous occasions that high-fat intake leads to positive energy balance which ultimately leads to enlarged body fat stores (Lissner et al, 1987;Dreon et al, 1988;Romieu et al, 1988;Tremblay et al, 1989). As suggested by Flatt (1991) and demonstrated by others (Schutz et al, 1992;Astrup et al, 1994), this fat gain promotes a reequilibration of energy intake to expenditure. It is also dif®cult to assess whether factors other than FA composition (ethnicity, social economic status, vegetarianism, etcF F F) are responsible for the observed trends.…”
Section: Discussionmentioning
confidence: 92%
“…70 Several studies have shown that there are neuroendocrine adaptations to a positive energy balance. Indeed, an increase in plasma free-fatty acids, 73 fat oxidation, 74,75 sympathetic nervous system activity, 76,77 insulinemia at euglycemia 78 and leptinemia 79 are all adaptations that contribute to promote over time the re-equilibration of energy balance in the person who gains weight. Because obesity is the common component of these adaptive mechanisms, an increase in body fat appears as a necessary adaptation to recover body weight stability when one is exposed to a lifestyle favoring a positive energy balance.…”
Section: Short Sleep Duration: Association With Glucose Homeostasismentioning
confidence: 99%